Vascular cell-specific roles of mineralocorticoid receptors in pulmonary hypertension. (June 2021) - Menon, Divya P.; Qi, Guanming; Kim, Seung K.; Moss, M. Elizabeth; Penumatsa, Krishna C.; Warburton, Rod R.; Toksoz, Deniz; Wilson, Jamie; Hill, Nicholas S.; Jaffe, Iris Z.; Preston, Ioana R.
Abnormalities that characterize pulmonary arterial hypertension include impairment in the structure and function of pulmonary vascular endothelial and smooth muscle cells. Aldosterone levels are elevated in human pulmonary arterial hypertension and in experimental pulmonary hypertension, while inhibition of the aldosterone-binding mineralocorticoid receptor attenuates pulmonary hypertension in multiple animal models. We explored the role of mineralocorticoid receptor in endothelial and smooth muscle cells in using cell-specific mineralocorticoid receptor knockout mice exposed to sugen/hypoxia-induced pulmonary hypertension. Treatment with the mineralocorticoid receptor inhibitor spironolactone significantly reduced right ventricular systolic pressure. However, this is not reproduced by selective mineralocorticoid receptor deletion in smooth muscle cells or endothelial cells. Similarly, spironolactone attenuated the increase in right ventricular cardiomyocyte area independent of vascular mineralocorticoid receptor with no effect on right ventricular weight or interstitial fibrosis. Right ventricular perivascular fibrosis was significantly decreased by spironolactone and this was reproduced by specific deletion of mineralocorticoid receptor from endothelial cells. Endothelial cell-mineralocorticoid receptor deletion attenuated the sugen/hypoxia-induced increase in the leukocyte-adhesion molecule, E-selectin, and collagen IIIA1 in the right ventricle. Spironolactone also significantly reduced pulmonary arteriolar muscularization, independent of endothelial cell-mineralocorticoid receptor or smooth muscle cell-mineralocorticoid receptor. Finally, the degree of pulmonary perivascular inflammation was attenuated by mineralocorticoid receptor antagonism and was fully reproduced by smooth muscle cell-specific mineralocorticoid receptor deletion. These studies demonstrate that in the sugen/hypoxia pulmonary hypertension model, systemic-mineralocorticoid receptor blockade significantly attenuates the disease and that mineralocorticoid receptor has cell-specific effects, with endothelial cell-mineralocorticoid receptor contributing to right ventricular perivascular fibrosis and smooth muscle cell-mineralocorticoid receptor participating in pulmonary vascular inflammation. As mineralocorticoid receptor antagonists are being investigated to treat pulmonary arterial hypertension, these findings support novel mechanisms and potential mineralocorticoid receptor targets that mediate therapeutic benefits in patients.